2017
DOI: 10.1021/acs.est.7b01303
|View full text |Cite
|
Sign up to set email alerts
|

History Matters: Pre-Exposure to Wastewater Enhances Pesticide Toxicity in Invertebrates

Abstract: Disturbance regimes determine communities' structure and functioning. Nonetheless, little effort has been undertaken to understand interactions of press and pulse disturbances. In this context, leaf-shredding macroinvertebrates can be chronically exposed to wastewater treatment plant effluents (i.e., press disturbance) before experiencing pesticide exposure following agricultural runoff (i.e., pulse disturbance). It is assumed that wastewater pre-exposure alters animals' sensitivity to pesticides. To test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In addition to organisms’ survival, their feeding on leaves was markedly influenced by neonicotinoid exposure and, in the case of Gammarus , similar to values seen in other studies ,, (see also Table ). Regarding THI, for instance, the calculated 7 day EC 50 deviated only marginally from that observed in one of our recent studies (see Table ), confirming the reported repeatability of the feeding assay . Furthermore, in contrast to the mortality data, complete concentration–response curves for the test organisms’ feeding rate could be obtained for most of the neonicotinoids and exposure scenarios (except for Chaetopteryx exposed to ACE and THI), allowing for a direct comparison of the EC x values (Table ) as well as the progression of the concentration–response curves (Figure ).…”
Section: Resultssupporting
confidence: 82%
“…In addition to organisms’ survival, their feeding on leaves was markedly influenced by neonicotinoid exposure and, in the case of Gammarus , similar to values seen in other studies ,, (see also Table ). Regarding THI, for instance, the calculated 7 day EC 50 deviated only marginally from that observed in one of our recent studies (see Table ), confirming the reported repeatability of the feeding assay . Furthermore, in contrast to the mortality data, complete concentration–response curves for the test organisms’ feeding rate could be obtained for most of the neonicotinoids and exposure scenarios (except for Chaetopteryx exposed to ACE and THI), allowing for a direct comparison of the EC x values (Table ) as well as the progression of the concentration–response curves (Figure ).…”
Section: Resultssupporting
confidence: 82%
“…10,11,50 The higher availability of refuge sections at the sites studied by Russo et al 48 may therefore explain the increased sensitivity instead of adaptation, as opposed to the populations investigated in Shahid et al 11 and the present study. Another study also reported increased sensitivity 51 to thiacloprid in G. pulex populations experiencing pre-exposure to wastewater. Organisms subjected to press disturbance are more likely less tolerant to superimposed pulse disturbances.…”
Section: Environmental Science and Technologymentioning
confidence: 82%
“…While there are studies that measured the feeding rates of gammarids, the values reported are very diverse and are affected not only by physical parameters such as temperature but also by chemical pollution ,, and microbial cover. , Because those parameters varied strongly over the whole test period and the pesticide concentrations found in both leaves and sediments were comparatively small, it was decided that for the modeling of the dietary uptake, a worst-case approach was warranted. Subsequently, the highest reported leaf-feeding rate of 0.43 ± 0.03 g leaves dw /g gammarids dw ·d was used and adjusted to g leaves dw /g gammarids ww ·d using the determined water content of the test gammarids.…”
Section: Methodsmentioning
confidence: 99%